2010
DOI: 10.2176/nmc.50.749
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery/Radiotherapy for Pituitary Adenomas: A Review of Recent Literature

Abstract: The recent clinical results are reviewed of stereotactic radiosurgery/radiotherapy for the treatment of pituitary adenomas. The outcomes of pituitary adenomas treated by stereotactic radiosurgery/radiotherapy with gamma knife, CyberKnife, or linear accelerator (LINAC) radiosurgery were evaluated from articles published after 2004. Each study was evaluated for the number of patients, radiosurgical parameter (marginal dose), length of follow up, tumor growth control, rate of hormonal normalization in secretary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…4. The first reports of CyberKnife treatment of pituitary adenomas are available [7,19,22]. Despite the few cases with short follow-up, it can be recognized that optimal radiation dose and application mode have to be elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…4. The first reports of CyberKnife treatment of pituitary adenomas are available [7,19,22]. Despite the few cases with short follow-up, it can be recognized that optimal radiation dose and application mode have to be elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that pituitary adenomas, such as acromegaly, can be safely and effectively treated with stereotactic radiosurgery (SRS) (1,2) . Frequently used radiosurgery systems for treating such brain lesions include Gamma Knife, (1,3–5) CyberKnife, (1,6,7) and linear accelerator (linac)‐based treatments (1,8,9) . Because each system involves higher‐than‐normal doses per fraction and steep dose gradients, (2,8) there is an increased importance to accurately delivering the treatment to the patient (2) .…”
mentioning
confidence: 99%
“…Several studies have reported that pa prescribed dose of 20-29 Gy to a pituitary adenoma resulted in an 82-100% tumor control rate, and therefore, in this planning study, we used a prescribed dose of 25 Gy to the target volume [1418]. …”
Section: Discussionmentioning
confidence: 99%